أثر اختلاف العامل النحوي في التفسير - الجبر، بدر بن ناصر (جامعة الإمام محمد بن سعود الإسلامية, 2021)
يدرس البحث تأثير العامل النحوي في تفسير كلام الله، ويبين أهمية العامل وأثره في قواعد الترجيح والاختلاف بين المفسرين، وأنه يمد المفسر بعدد من المعاني المحتملة، ولا غنى عن معرفة العامل وتحديده في التفسير. ويتناول مجموعة من الآيات القرآنية التي تعددت توجيهات المفسرين تبعاً لتعدد العامل النحوي المحتمل لها؛ للوقوف على هذه التوجيهات وتلمس التعليلات التي أبداها المفسرون، والنظر في هذه القرائن التي سيقت لتلك الأوجه والاحتمالات. وحرص الباحث على تنويع التفاسير والمصادر التي توضح قيمة العامل النحوي وأثره في التفسير، وتنويع الأوجه التي يظهر فيها الاختلاف والتأثر، فمنها: أثر عامل المفرد وعامل الجملة وعامل شبه الجملة، وأثر اختلاف المعنى المعجمي للعامل، واحتمال تعديته ولزومه، ودرس هذه الآيات دراسة مفصلة، وبين فيها آراء المفسرين، وكشف عن أثر تعدد العامل النحوي أو الخلاف فيه في معنى الآية مستعيناً بما ذكره النحويون في إعرابهم كتاب الله.
The research studies the effect of syntactic factor difference in the explanation of Allah's words, showing the importance of factor and its effect in weighting and variation among interpreters, and it gives the interpreter several potential meanings and the importance of identifying the factor and determining it in explanation. The research addresses a group of Quranic verses that had multiplied of interpreters' guidelines according to multiple possible syntactic factors, to stand on these guidelines and seek the reasons that made by the interpreters, and consider these clues for those possibilities and aspects. The researcher made sure of variation of explanation and resources that show the value of syntactic factor and its effect in explanation and diversity of aspects that show the differences and effect, and they are: the effect of factor in singular, sentence and phrase, the effect of lexical meaning difference of factors, the possibility of its being transitive and intransitive, studied these verses detailed study, showed the opinions of interpreters and showed the effect of variation of syntactic factor or disagreement on the meaning of verse using what interpreters have mentioned in their explanation of Allah's book.
Keywords: القرآن الكريم -- التفاسير اللغوية -- النحو العربي -- إعراب القرآن